AN APPROACH TO THE IMPLEMENTATION OF A COMPETENCY-BASED APPROACH IN THE LEARNING MANAGEMENT SYSTEM - Kopp, Andrii; Parashchych, Mykyta; Zvertsev, Herman; Motalyhin, Yevhen; Strelnikova, Anna (Ukrainian Information Security Research Journal, 2023)
This paper solves the urgent problem of improving the tracking of the process of acquiring competencies by students through the means of analyzing the learning management system data and visualizing the results of the learning process. The object of the study is to track the process of acquiring competencies by students. The subject of the study includes software components for the implementation of a competency-based approach in the learning management system. The purpose of the study is to improve the tracking of the process of acquiring competencies by students by analyzing the data of the Learning Management System (LMS) and visualizing the results of the learning process. Thus, to achieve this goal, we analyzed the technologies for processing learning data from LMS, analyzed the features of modeling the learning process based on Petri nets and BPMN (Business Process Model and Notation), determined a data structure, and proposed an algorithm for building a model and visualizing the learning process data. The developed software components allow processing of learning process data from LMS, building models and visualizations of learning process data, saving the results to data warehouses, depicting the learning process model, and visualizing learning process data for further analytical processing.